Modelling Reporting Delays in a Multilevel Structured Surveillance System - Application to Portuguese HIV-AIDS Data - Oliveira, Alexandra (2019)
In a deeply interconnected world of people and goods, infectious diseases constitute a serious threat. An active vigilance is required. The collection of adequate data is vital and coordinated by surveillance systems. It is widely-acknowledged that every case-reporting system has some degree of under-reporting and reporting delay in particular in HIV-AIDS Portuguese Surveillance System. To better understand the processes generating the reporting delays, which is an administrative process, it was used a flexible continuous time fully parametric survival analysis approach. It was taken into consideration the hierarchical administrative and organizational structure of the system as well as the relevant changes in the procedures throughout the time. The best multilevel structure to represent reporting delays in continuous time is the model where the individuals are nested into Reporting Entities (20.24% of the variance) which are nested into Type of services (8% of the variance) with the log-normal distribution.